2008
DOI: 10.1016/j.ijindorg.2006.10.004
|View full text |Cite
|
Sign up to set email alerts
|

To build or not to build: Normative and positive theories of public–private partnerships

Abstract: This paper analyzes whether the two tasks of building infrastructures which are socially useful in providing public services and managing these assets should be bundled or not. When performance contracts can be written, both tasks should be performed altogether by the same firm if a better design of the infrastructure helps also to save on operating costs. Otherwise, tasks should be kept apart and undertaken by different units. In incomplete contracting environments we isolate conditions under which either the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
186
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(203 citation statements)
references
References 24 publications
8
186
0
9
Order By: Relevance
“…It is shown that the bundling of tasks within a PPP is optimal in the case of a positive externality, whereas with a negative externality one should choose the traditional way of service provision. The same result is obtained in Martimort and Puoyet (2008) in a agency setting with complete contracts. Beyond that the paper by Martimort and Puoyet also considers different ownership structures and addresses some aspects of the political economy of PPPs.…”
Section: Introductionsupporting
confidence: 78%
“…It is shown that the bundling of tasks within a PPP is optimal in the case of a positive externality, whereas with a negative externality one should choose the traditional way of service provision. The same result is obtained in Martimort and Puoyet (2008) in a agency setting with complete contracts. Beyond that the paper by Martimort and Puoyet also considers different ownership structures and addresses some aspects of the political economy of PPPs.…”
Section: Introductionsupporting
confidence: 78%
“…There is a burgeoning literature on the "boundary of the organization" and how public entities provide services (Hart, Shleifer and Vishny 1997, Lopez de Silanes, Shleifer and Vishny 1997, Nelson 1997, Brown and Potoski 2003, Martimort and Pouyet 2008, David and Chiang 2009, Levin and Tadelis 2010, Iossa and Martimort 2012, but nearly every empirical investigation has focused on one ownership type. These studies cannot address what is essentially "public" or "nonprofit" about choices because they lack a control group of profit maximizers.…”
Section: Introductionmentioning
confidence: 99%
“…According to Grout (1997);Hart (2003); Bennett and Iossa (2006);Bentz et al (2005); Martimort and Pouyet (2008); Iossa and Martimort (2008) all their studies point out and consider internal life sequence cost consideration, ownership of the infrastructure and compensation costs as possible favourable arguments of PPPs.…”
Section: Internalize Life Sequence Cost Considerations During Construmentioning
confidence: 99%